2017
DOI: 10.3389/fimmu.2016.00676
|View full text |Cite
|
Sign up to set email alerts
|

Microglial CD206 Gene Has Potential as a State Marker of Bipolar Disorder

Abstract: The pathophysiology of bipolar disorder, especially the underlying mechanisms of the bipolarity between manic and depressive states, has yet to be clarified. Microglia, immune cells in the brain, play important roles in the process of brain inflammation, and recent positron emission tomography studies have indicated microglial overactivation in the brain of patients with bipolar disorder. We have recently developed a technique to induced microglia-like (iMG) cells from peripheral blood (monocytes). We introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…It is worth mentioning the pioneering work of Ohgidani et al., showing, using microglial‐like cells derived from peripheral monocytes, that the proinflammatory M1 microglia is dominant in the manic as compared with depressive state . Although, we have no direct evidence relating HLA genetics to microglial polarization, our finding concerning genetic association of 57.1 and 8.1 haplotypes (inflammatory haplotypes) with rapid cycling may be pertinent.…”
Section: Discussionmentioning
confidence: 61%
“…It is worth mentioning the pioneering work of Ohgidani et al., showing, using microglial‐like cells derived from peripheral monocytes, that the proinflammatory M1 microglia is dominant in the manic as compared with depressive state . Although, we have no direct evidence relating HLA genetics to microglial polarization, our finding concerning genetic association of 57.1 and 8.1 haplotypes (inflammatory haplotypes) with rapid cycling may be pertinent.…”
Section: Discussionmentioning
confidence: 61%
“…On the basis of such pilot investigations, we have hypothesized that inflammation and oxidative stress may be linked to the underlying pathophysiology of hikikomori , similarly to other psychiatric disorders . Microglia play crucial roles in brain inflammation via releasing free radicals and inflammatory cytokines, such as interleukin‐6 and tumor necrosis factor‐α, and activation of microglia has recently been proposed to exist in various psychiatric disorders, including schizophrenia, depression, bipolar disorder, and autism . In addition, microglial overactivation is proposed to exist in the brains of suicide victims and suicidal individuals, especially via the tryptophan–kynurenine pathway .…”
Section: Multidimensional Understandings Of Hikikomorimentioning
confidence: 99%
“…76,[83][84][85][86][87] Microglia play crucial roles in brain inflammation via releasing free radicals and inflammatory cytokines, such as interleukin-6 and tumor necrosis factor-α, 88,89 and activation of microglia has recently been proposed to exist in various psychiatric disorders, including schizophrenia, depression, bipolar disorder, and autism. 76,86,[90][91][92][93][94][95][96][97] In addition, microglial overactivation is proposed to exist in the brains of suicide victims and suicidal individuals, especially via the tryptophan-kynurenine pathway. [98][99][100][101][102][103] As noted above, a recent epidemiological data analysis showed that hikikomori sufferers are more likely to have suicide risk, 29 thus similar biological mechanisms via microglial activation may exist in hikikomori.…”
Section: Biological Understandings Of Hikikomorimentioning
confidence: 99%
“…The pathophysiology of BD is yet to be well understood, while recent studies have indicated that abnormal immunological functions may be a contributing factor [38][39][40][41][42]. Recently, positron emission tomography (PET) studies have shown microglial overactivation in the brain of patients with various psychiatric disorders [43][44][45]; [9] including bipolar disorder [42].…”
Section: Mechanisms Of Neuroinflammationmentioning
confidence: 99%
“…The pathophysiology of BD is yet to be well understood, while recent studies have indicated that abnormal immunological functions may be a contributing factor [38][39][40][41][42]. Recently, positron emission tomography (PET) studies have shown microglial overactivation in the brain of patients with various psychiatric disorders [43][44][45]; [9] including bipolar disorder [42]. Consistent with the previous studies, it was revealed that in BD, the immune system is chronically activated by microglia, which in turn produces cytokines that render the brain to a vulnerable and unstable state, precipitating mood disturbances [45][46][47].…”
Section: Mechanisms Of Neuroinflammationmentioning
confidence: 99%